The impact of simulation education on self‐efficacy towards teaching for nurse educators. (23rd March 2018) - Garner, S.L.; Killingsworth, E.; Bradshaw, M.; Raj, L.; Johnson, S.R.; Abijah, S.P.; Parimala, S.; Victor, S.
Abstract : Aim: The objective of this study was to assess the impact of a simulation workshop on self‐efficacy towards teaching for nurse educators in India. Additionally, we sought to revise and validate a tool to measure self‐efficacy in teaching for use with a global audience. Background: Simulation is an evidence‐based teaching and learning method and is increasingly used in nursing education globally. Introduction: As new technology and teaching methods such as simulation continue to evolve, it is important for new as well as experienced nurse educators globally to have confidence in their teaching skills and abilities. Methods: The study included (1) instrument revision, and measures of reliability and validation, (2) an 8‐h faculty development workshop intervention on simulation, (3) pre‐ and post‐survey of self‐efficacy among nurse educators, and (4) investigation of relationship between faculty socio‐demographics and degree of self‐efficacy. Results: The modified tool showed internal consistency ( r = 0.98) and was validated by international faculty experts. There were significant improvements in total self‐efficacy ( P < 0.001) and subscale scores among nurse educators after the simulation workshop intervention when compared to pre‐survey results. No significant relationships were found between socio‐demographic variables and degree of self‐efficacy. Discussion: Strong self‐efficacy in teaching among nurse educators is crucial for effective learning to occur. Conclusions and implications for nursing: Results indicated the simulation workshop was effective in significantly improving self‐efficacy towards teaching for nurse educators using an internationally validated tool. Implications for nursing policy: The Minister of Health in India recently called for improvements in nursing education. Introducing nursing education on simulation as a teaching method in India and globally to improve self‐efficacy among teachers is an example of a strategy towards meeting this call.